Synthesis of nanostructured zirconium phosphate

The preparation of nanostructured zirconium phosphate by flame spray pyrolysis method solves the problems of poor industrial scale production and electrochemical performance in the prior art, and achieves efficient and uniform material preparation and excellent battery performance.

CN119497700APending Publication Date: 2025-02-21EVONIK OPERATIONS GMBH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380052320.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-07
Filing Date
2023-06-29
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently produce nano-size and nano-structured zirconium phosphate with excellent electrochemical properties on industrial scale, and wet chemical methods lead to uneven distribution of material particle size and high compaction density, affecting battery performance.

Method used

Flame spray pyrolysis method is adopted to perform flame spray pyrolysis by a specific combination of zirconium carboxylate, organophosphate esters and low water content solvents to prepare zirconium phosphate particles with small particle size, high BET surface area and low compaction density.

Benefits of technology

The production of nanostructured zirconium phosphate with excellent electrochemical properties has been achieved, which significantly improves its dispersion and cycle stability in the battery, reduces the LiOH/Li2CO3 content, and improves the performance and life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119497700A_ABST
    Figure CN119497700A_ABST
Patent Text Reader

Abstract

The invention relates to a method for producing zirconium phosphate by flame spray pyrolysis, to zirconium phosphate obtainable by this method and to the use thereof in batteries, in particular for encapsulating lithium mixed oxide particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a process for producing zirconium phosphate by flame spray pyrolysis, to the zirconium phosphate obtainable by this process and to its use in batteries, in particular for encapsulating lithium mixed oxide particles. Background Art

[0002] Lithium-ion secondary batteries are one of the most important types of batteries currently in use. Lithium-ion secondary batteries are usually composed of a negative electrode (anode) made of carbon material or lithium metal alloy, a positive electrode (cathode) made of lithium-metal oxide, an electrolyte in which lithium salts are dissolved in an organic solvent, and a separator that provides a passage for lithium ions between the positive and negative electrodes during the charging and discharging process.

[0003] In an effort to develop secondary batteries with improved inherent safety and energy density, considerable progress has recently been made in using solid electrolytes instead of liquid electrolytes. In such a system, secondary lithium batteries with electrodes made of lithium metal or lithium metal alloys are considered to provide high energy density and are particularly suitable. Such all-solid-state lithium-ion secondary batteries should have good ionic conductivity at the interface between the electrode active material and the electrolyte in order to have the desired load characteristics. As described in JP 4982866B2, this high ionic conductivity can be achieved by coating the surface of the active electrode material with some lithium-containing compounds such as LiTi2(PO4)3.

[0004] A major general problem with cathode materials is aging and, therefore, loss of performance during cycling. This phenomenon is particularly relevant for high-nickel NMCs. During cycling, cathode materials are subject to several electrochemical degradation mechanisms. Surface transformations, such as 4+ Reduction and oxygen loss in a highly delithiated state and rearrangement of transition metals to form a NiO-like phase destabilize the crystal structure. This phase transition is associated with the initiation of cracks in the positive electrode particles and subsequent particle disintegration. In addition, the electrolyte decomposes on the reaction surface of the NMC, and the electrolyte decomposition products are deposited at the interface, which leads to increased resistance. In addition, the conductive salt LiPF6 commonly used in liquid electrolytes reacts with trace amounts of H2O present in all commercial preparations to form HF. The acidic HF formed causes lattice distortion in the positive electrode material by dissolving transition metal ions from the surface of the positive electrode material into the electrolyte. All of these degradation mechanisms lead to a reduction in capacity, performance, and cycle life.

[0005] Surface coating of cathode active materials has been demonstrated to be an extremely important approach to address this aging problem by inhibiting direct contact between the active material surface and the liquid electrolyte.

[0006] WO 2021 / 089886 describes a method for producing lithium zirconium phosphate by flame spray pyrolysis using lithium, phosphorus and zirconium compounds as precursors. The method described therein is suitable for producing lithium zirconium phosphate with acceptable optical properties, but the production volume is limited in the case where the desired product should be as white as possible. The use of higher flow rate values ​​of the gas stream introduced into the flame pyrolysis produces a gray product that is not suitable for industrial applications. The gray nature is caused by incomplete combustion of the precursors and is attributed to carbon residues in the product. In particular, due to the increasing demand for electronics and energy storage devices, there is a greater need for materials with optimized properties that can be obtained at high production volumes on an industrial scale.

[0007] A promising material that can also be used in batteries is zirconium phosphate. K. Min et al. describe Li-reactive coatings with metal phosphates in Sci Rep. 2017; 7: 7151. Cobalt phosphate, manganese phosphate and iron phosphate appear to be good coating materials for Li-reactive coatings at the interface of the cathode active material.

[0008] US2007 / 0224483A1 describes the preparation of organic solutions of precursors of tetravalent metal phosphates and pyrophosphates of different metals. An important property of these solutions is that the compounds are formed when the solvent evaporates, thereby allowing the compounds to be inserted into the pores of porous membranes, polymer membranes and electrode interfaces of fuel cells.

[0009] In addition, the common strategies described in the literature for obtaining zirconium pyrophosphate coated cathode materials require laborious wet chemical methods with long reaction times followed by drying and calcination steps at high temperatures. Such a wet chemical method for producing zirconium pyrophosphate is described by Maati Houda et al. in Catalysis Letters, Vol. 148, No. 2, pp. 699-711 (Nanostructured Zirconium pyrophosphate catalyzed diastereoselective synthesis of [beta]-Amino ketones via One-Pot Three-Component Mannich Reaction).

[0010] Such wet chemical processes result in zirconium pyrophosphate powders with a broad particle size distribution and an unfavorable tamped density. Especially for use in electrodes and batteries, specific property profiles are required, which cannot be covered by materials produced by wet chemical methods. Materials produced by wet chemical methods generally have denser aggregates, resulting in poorer dispersibility and thus unfavorable non-uniform coatings of these materials on battery electrodes.

[0011] Therefore, these methods are not only time-consuming and expensive, but also do not provide materials for batteries, making these methods rather unsuitable for industrial applications. Summary of the invention

[0012] The problem to be solved by the present invention is to provide an improved process for the industrial production of nanosized and nanostructured zirconium phosphates which can be easily used in batteries.

[0013] In particular, the process should provide zirconium phosphate particles having a relatively small particle size, a high BET surface area and a low tapped density.

[0014] Spray pyrolysis is a known process for producing various metal oxides and certain metal salts.

[0015] In spray pyrolysis, metal compounds in the form of fine droplets are introduced into a high-temperature zone, where they are oxidized and / or hydrolyzed to give the corresponding metal oxides or salts. A special form of this process is flame spray pyrolysis, in which the droplets are fed into a flame formed by igniting a fuel gas and an oxygen-containing gas.

[0016] During the experiment, it was surprisingly found that zirconium phosphate with desired particle properties can be directly prepared by flame spray pyrolysis when a special combination of precursors and solvents is used. The nanostructured zirconium pyrophosphate prepared by the flame method thus pyrolyzed shows a unimodal and narrow particle size distribution, as well as excellent dispersibility during the dry coating process. This results in complete deagglomeration of the zirconium pyrophosphate aggregates, and ultimately enables a complete and uniform zirconium pyrophosphate coating to be formed around the lithium mixed oxide positive electrode particles prepared by powder dry coating. This high-intensity dry coating method is very time-saving. In addition, the material of the present invention shows a high affinity for reacting with residual lithium ion-containing substances on the surface of the positive active material, which would otherwise interfere with the function of the battery. Without being bound by theory, it is expected that the lithium ion-containing substance will react with the zirconium phosphate to partially form lithium zirconium phosphate, which is a commonly known battery material.

[0017] Zirconium phosphate

[0018] The present invention provides a zirconium phosphate having a general formula of ZrP2O7 prepared by pyrolysis, characterized in that the zirconium phosphate

[0019] - in the form of aggregated primary particles,

[0020] -BET surface area (DIN 9277:2014) 5m 2 / g-100m 2 / g,

[0021] -Numerical average particle size d 50 = 0.03 μm - 2 μm, as determined by static light scattering (SLS), and

[0022] - Tamped density (DIN ISO 787-11:1995) is 20 g / L-200 g / L.

[0023] The zirconium phosphate of the present invention can be obtained by the method of the present invention described below.

[0024] The BET surface area of ​​the zirconium phosphate prepared by pyrolysis of the present invention is 5 m 2 / g-100m 2 / g, preferably 7m 2 / g-80m 2 / g, more preferably 15-60m 2 / g. The BET surface area can be determined in accordance with DIN 9277:2014 by nitrogen adsorption according to the Brunauer-Emmett-Teller procedure.

[0025] The pyrolytically prepared zirconium phosphate of the present invention is in the form of aggregated primary particles, the numerical mean diameter of the primary particles is generally 1-100 nm, preferably 3-70 nm, more preferably 5-50 nm, as determined by transmission electron microscopy (TEM). The numerical mean diameter can be determined by calculating the average size of at least 500 particles analyzed by TEM.

[0026] The numerical average particle size d of the zirconium phosphate in aggregated and optionally agglomerated form is 50 It is about 0.03 μm-2 μm, more preferably 0.04 μm-1 μm, and even more preferably 0.05 μm-0.5 μm, as determined by static light scattering (SLS) after ultrasonic treatment of a mixture consisting of 5 wt % of the particles and 95 wt % of a 0.5 g / L sodium pyrophosphate aqueous solution at 25°C for 300 s.

[0027] Agglomerates and partial aggregates can be disrupted, for example by grinding or sonicating the particles, to produce particles of smaller size and narrower size distribution.

[0028] The tamped density of the pyrolytically prepared zirconium phosphate according to the invention is 20 g / L to 200 g / L, preferably 25 g / L to 150 g / L, even more preferably 30 g / L to 100 g / L, still more preferably 40 g / L to 80 g / L. The tamped density of powdery or coarse-grained granular materials can be determined according to DIN ISO 787-11: 1995 "General methods of test for pigments and extenders--Part 11: Determination of tamped volume and apparent density after tamping". This involves measuring the apparent density of the bed after stirring and tamping.

[0029] Process for producing zirconium phosphate

[0030] The present invention also provides a method for producing the zirconium phosphate of the present invention by flame spray pyrolysis, wherein the zirconium phosphate comprising

[0031] - at least one zirconium compound chosen from carboxylates, wherein each of these zirconium carboxylates contains 5 to 20 carbon atoms,

[0032] -organophosphates,

[0033] -Solvents containing less than 10% by weight of water

[0034] The solution was subjected to flame spray pyrolysis.

[0035] During the flame spray pyrolysis process according to the invention, a solution of a zirconium compound (metal precursor) and a phosphorus source in the form of fine droplets is generally introduced into a flame which is formed by igniting a fuel gas and an oxygen-containing gas, wherein the metal precursor used together with the phosphorus source is oxidized and / or hydrolyzed to give the corresponding zirconium phosphate.

[0036] The reaction initially forms highly dispersed, approximately spherical primary particles, which coalesce to form aggregates in the further course of the reaction. The aggregates can then accumulate into agglomerates. In contrast to agglomerates, which can usually be separated into aggregates relatively easily by introducing energy, aggregates can only be further decomposed (if at all) by intensive introduction of energy.

[0037] The resulting aggregate compound may be referred to as "fume phase" or "pyrolytically produced" zirconium phosphate.

[0038] Flame spray pyrolysis processes are generally described in WO 2015173114 A1 and elsewhere.

[0039] The flame spray pyrolysis method of the present invention preferably comprises the following steps:

[0040] a) atomizing a solution of a zirconium compound by means of an atomizer gas to obtain an aerosol,

[0041] b) reacting the aerosol in the reaction space of the reactor with a flame obtained by igniting a mixture of a fuel gas and an oxygen-containing gas to obtain a reaction stream,

[0042] c) cooling the reaction stream, and

[0043] d) The solid zirconium phosphate is subsequently removed from the reaction stream.

[0044] Examples of fuel gases are hydrogen, methane, ethane, natural gas and / or carbon monoxide. Hydrogen is particularly preferably used. Fuel gases are particularly useful in embodiments where a high degree of crystallinity of the zirconium phosphate to be produced is desired.

[0045] The oxygen-containing gas is typically air or oxygen-enriched air. The oxygen-containing gas is particularly useful in embodiments where, for example, a high BET surface area of ​​the zirconium phosphate to be produced is desired. The total amount of oxygen is typically selected so that it is at least sufficient to completely convert the fuel gas and the metal precursor.

[0046] In order to obtain an aerosol, the evaporated solution containing the metal precursor can be mixed with an atomizer gas such as nitrogen, air and / or other gases. The average droplet size of the fine droplets of the resulting aerosol is preferably 1-120 μm, particularly preferably 30-100 μm. The droplets are usually produced using a single-material nozzle or a multi-material nozzle. In order to increase the solubility of the metal precursor and obtain a suitable viscosity for solution atomization, the solution can be heated.

[0047] The metal precursor employed in the method of the present invention comprises at least one zirconium carboxylate, each of which contains from 5 to 20 carbon atoms.

[0048] The zirconium carboxylate used in the process according to the invention may be a linear, branched or cyclic valerate (C5), hexanoate (C6), heptanoate (C7), octanoate (C8), nonanoate (C9), decanoate (D10), undecanoate (C11), dodecanoate (C12), tridecanoate (C13), tetradecanoate (C14), pentadecanoate (C15), hexadecanoate (C16), heptadecanoate (C17), octadecanoate (C18), nonadecanoate (C19), eicosanoate (C20) and mixtures thereof of lithium and / or zirconium. Most preferably, zirconium 2-ethylhexanoate (C8) is used.

[0049] The metal precursor used may contain other salts of zirconium, such as nitrates, carbonates, chlorides, bromides, or other organometallic compounds, such as alkoxides, for example ethoxide, n-propoxide, isopropoxide, n-butoxide and / or tert-butoxide.

[0050] In the context of the present invention, the term "organophosphate" relates to any compound having at least one group (R) containing at least one carbon atom bonded to the phosphorus atom of the unit P(=O) via an oxygen atom, for example compounds of the general formula (RO)3P(=O) or (RO)(P(=O))2, wherein R is a group containing at least one carbon atom, for example methyl or ethyl.

[0051] The organic phosphate used in the method of the present invention is preferably selected from esters of phosphorous acid (H3PO3), orthophosphoric acid (H3PO4), metaphosphoric acid (HPO3), pyrophosphoric acid (H4P2O7), polyphosphoric acid and mixtures thereof.

[0052] The organic phosphate ester may be selected from alkyl esters such as methyl esters, ethyl esters, propyl esters, butyl esters, hexyl esters, aryl esters such as phenyl esters, mixed alkyl / aryl esters, and mixtures thereof.

[0053] The organic phosphate ester is preferably an ester having a group containing 1 to 10 carbon atoms, and most preferably an ester having an alkyl group containing 1 to 10 carbon atoms.

[0054] It was surprisingly found that the use of an organophosphate as phosphorus source is crucial for obtaining small zirconium phosphate particles with a high BET surface area and a low tapped density.

[0055] The solvent mixture used in the process of the present invention may be selected from linear or cyclic, saturated or unsaturated, aliphatic or aromatic hydrocarbons, carboxylic acid esters, ethers, alcohols, carboxylic acids and mixtures thereof.

[0056] The solvent mixture used in the present invention contains less than 10% by weight of water, preferably less than 5% by weight of water, more preferably less than 3% by weight of water, even more preferably less than 2% by weight of water, and still more preferably less than 1% by weight of water. The low water content prevents the undesired hydrolysis of the zirconium carboxylate in the metal precursor solution.

[0057] The total metal content of zirconium in the metal precursor solution is preferably 1 wt%-30 wt%, more preferably 2 wt%-20 wt%, even more preferably 3 wt%-15 wt%. "Total metal content" refers to the total weight proportion of all zirconium contained in the metal precursor in the solution used.

[0058] The solvent mixture used for the method of the present invention may additionally contain a chelating agent, i.e. a compound capable of forming two or more coordination bonds with the metal ion. Examples of such chelating agents are, for example, diamines such as ethylenediamine, ethylenediaminetetraacetic acid (EDTA) and 1,3-dicarbonyl compounds such as acetylacetone and alkyl acetoacetates. Most preferably, acetylacetone is used as such a chelating agent.

[0059] It was observed that in the presence of such a chelating agent, the zirconium compound showed better solubility and no precipitation after a relatively long storage time.

[0060] The use of a specific combination of metal precursors, phosphorus source and solvent in the process of the present invention allows ensuring good solubility of all precursors and achieving the desired particle properties of the resulting zirconium phosphate, such as small particle size, high BET surface area and low tapped density.

[0061] The method of the present invention may also comprise a step of heat treating the zirconium phosphate produced by flame spray pyrolysis. This further heat treatment is preferably carried out at a temperature of 200° C. to 1200° C., more preferably at 250° C. to 1100° C., even more preferably at 350° C. to 900° C. The heat treatment according to the method of the present invention allows obtaining a heat-treated zirconium phosphate having the desired properties, in particular the desired crystal structure.

[0062] The method of the present invention may comprise a further step of grinding, preferably ball milling, the heat treated zirconium phosphate. Ball milling is preferably carried out using ZrO2 balls, for example with a diameter of about 0.5 mm, in a suitable solvent such as ethanol or isopropanol.

[0063] Zirconium phosphate in lithium-ion batteries

[0064] The invention also provides the use of the zirconium phosphate according to the invention in lithium ion batteries, in particular as a component of a solid electrolyte of a lithium ion battery, as an additive in a liquid or gel electrolyte or as a component of an electrode of a lithium ion battery.

[0065] The invention also provides a lithium ion battery comprising the zirconium phosphate according to the invention or the zirconium phosphate obtainable by the process of the invention.

[0066] The lithium ion battery of the present invention may contain an active positive electrode (positive electrode), a negative electrode, a separator, and an electrolyte containing a lithium-containing compound.

[0067] The positive electrode (cathode) of a lithium-ion battery generally includes a current collector and an active positive electrode material layer formed on the current collector.

[0068] The current collector may be an aluminum foil, a copper foil, a nickel foil, a stainless steel foil, a titanium foil, a polymer substrate coated with a conductive metal, or a combination thereof.

[0069] The active cathode material may include materials capable of reversibly inserting / deinserting lithium ions, and is well known in the art. Such active cathode materials may include transition metal oxides, such as mixed oxides including Ni, Co, Mn, V or other transition metals and optionally lithium. The mixed lithium transition metal oxides preferably used as active cathode materials are selected from lithium-cobalt oxide, lithium-manganese oxide, lithium-nickel-cobalt oxide, lithium-nickel-manganese-cobalt oxide (NMC), lithium-nickel-cobalt-aluminum oxide, lithium-nickel-manganese oxide, lithium iron phosphate, lithium manganese oxide or mixtures thereof.

[0070] The negative electrode of the lithium-ion battery can include any suitable material commonly used in lithium-ion secondary batteries that can reversibly embed / de-embed lithium ions. Typical examples thereof are carbonaceous materials, including crystalline carbon, such as natural or artificial graphite in the form of plate-like, sheet-like, spherical or fibrous graphite; amorphous carbon, such as soft carbon, hard carbon, mesophase pitch carbide, coke, etc., or mixtures thereof. In addition, lithium metal, lithium layer or conversion material (such as Si or Sn) can be used as negative electrode active material.

[0071] The present invention also provides an electrode of a lithium ion battery, such as a positive electrode or a negative electrode, comprising the zirconium phosphate of the present invention. Specifically, the zirconium phosphate of the present invention can be a dopant or coating material of an electrode.

[0072] Throughout the experiments, it was surprisingly found that the pyrolysis-produced zirconium phosphate could be successfully used to coat mixed lithium transition metal oxides, which can be used as positive electrodes for lithium batteries.

[0073] Thus, the present invention provides a method for producing a coated mixed lithium transition metal oxide, wherein the mixed lithium transition metal oxide and pyrolytically produced zirconium phosphate are dry mixed.

[0074] Dry Mix

[0075] Dry mixing is understood to mean that no liquid is added or used during the mixing process, i.e. for example substantially dry powders are mixed together. However, trace amounts of moisture or some liquid other than water may be present in the mixed materials, or these may include water of crystallization.

[0076] The dry mixing method of the present invention has some advantages over mixing methods involving wet coating (e.g. coating with a dispersion containing a metal oxide). Such wet coating methods inevitably involve the use of solvents, which must be evaporated after the coating process is completed. Therefore, the dry coating method of the present invention is simpler and more economical than the wet coating methods known in the prior art. On the other hand, it was found that the dry coating method of the present invention also provides a better distribution of zirconium phosphate particles on the surface of the active material, such as a mixed lithium transition metal oxide.

[0077] For example, dry mixing can be carried out in a mixing unit with a specific electrical power of 0.05-1.5 kW / kg mixed material.

[0078] If the specific electrical power used is less than 0.05 kW / kg of mixed negative electrode material, this results in an uneven distribution of zirconium phosphate on top of the active material particles, which may not be firmly bonded to the core material of the active material particles. A specific electrical power of more than 1.5 kW / kg of mixed negative electrode material leads to poor electrochemical properties. In addition, there is a risk that the coating becomes brittle and easily breaks. The nominal electrical power of the hybrid unit can vary over a wide range of, for example, 0.1 kW to 1000 kW. Therefore, a hybrid unit with a nominal power of 0.1-5 kW can be used on a laboratory scale, or a hybrid unit with a nominal electrical power of 10-1000 kW can be used for a production scale. The nominal electrical power is the maximum absolute electrical power on the nameplate of the hybrid unit.

[0079] The volume of the mixing unit can vary within a wide range. For example, the volume of the mixing unit can be between 0.1 L and 2.5 m 3 For example, the volume of the mixing unit may be 0.1-10 L on a laboratory scale, or 0.1-2.5 m for a production scale. 3 .

[0080] Preferably, in the method according to the invention, the forced mixer is used in the form of an intensive mixer with high-speed mixing tools. It has been found that a mixing tool speed of 5-30 m / s, more preferably 10-25 m / s, produces the best results. Examples of commercially available mixing units suitable for the method of the invention include Henschel mixers and Eirich mixers. The Eirich mixer can be, for example, a high-intensity Eirich mixer.

[0081] The mixing time may vary and may preferably be from 0.1 to 120 minutes, more preferably from 0.2 to 60 minutes, most preferably from 0.5 to 10 minutes.

[0082] After mixing, the mixture may be subjected to a heat treatment in order to improve the bonding of the coating to the active material particles. However, this treatment is optional in the method according to the invention, since in this method the nanostructured zirconium phosphate produced by pyrolysis adheres to the active material particles with sufficient firmness. In the case of a heat treatment of the mixture, the temperature is generally in the range of 200-1000° C. for up to 48 hours. The heat treatment may be carried out in the presence of different types of gases, such as, for example, nitrogen, oxygen or forming gas.

[0083] The present invention also provides an electrolyte for a lithium ion battery comprising the zirconium phosphate of the present invention.

[0084] The electrolyte of a lithium-ion battery can be in liquid, gel or solid form.

[0085] The liquid electrolyte of the lithium-ion battery may include any suitable organic solvent commonly used in lithium-ion batteries, such as anhydrous ethylene carbonate (EC), dimethyl carbonate (DMC), propylene carbonate, ethyl methyl carbonate, diethyl carbonate, gamma-butyrolactone, dimethoxyethane, fluoroethylene carbonate, vinylethylene carbonate, or mixtures thereof.

[0086] The gel electrolyte includes a gelling polymer.

[0087] Solid electrolytes for lithium-ion batteries may include oxides, such as lithium metal oxides, sulfides, phosphates, or solid polymers.

[0088] The liquid or polymer gel electrolyte of lithium ion batteries usually contains lithium salts. Examples of such lithium salts include lithium hexafluorophosphate (LiPF6), lithium bis (trifluoromethylsulfonyl) imide (LiTFSI), lithium bis (fluorosulfonyl) imide (LiFSI), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), Li2SiF6, lithium trifluoromethanesulfonate, LiN(SO2CF2CF3)2, lithium nitrate, lithium bis (oxalate) borate, lithium cyclodifluoromethane-1,1-bis (sulfonyl) imide, lithium cyclohexafluoropropane-1,1-bis (sulfonyl) imide and mixtures thereof.

[0089] Lithium-ion batteries, especially those with a liquid or gel electrolyte, may also include a separator that prevents the two electrodes from coming into direct contact, which would result in an internal short circuit.

[0090] The material of the diaphragm can include polyolefin resin, fluorinated polyolefin resin, polyester resin, polyacrylonitrile resin, cellulose resin, nonwoven fabric or its mixture. Preferably, the material includes polyolefin resin such as polyethylene or polypropylene-based polymer, fluorinated resin such as polyvinylidene fluoride polymer or polytetrafluoroethylene, polyester resin such as polyethylene terephthalate and polybutylene terephthalate, polyacrylonitrile resin, cellulose resin, nonwoven fabric or its mixture.

[0091] The lithium ion battery according to the present invention may include a liquid electrolyte, a gel electrolyte or a solid electrolyte. In the context of the present invention, a liquid mixture of an uncured polymerized or cross-linked lithium salt and an organic solvent is referred to as a "liquid electrolyte". A gel or solid mixture comprising a cured polymerized or cross-linked compound or a mixture thereof, an optional solvent and a lithium salt is referred to as a "gel electrolyte". Such a gel electrolyte can be prepared by polymerization or cross-linking of a mixture containing at least one reactive compound, i.e., a polymerizable or cross-linkable compound, and a lithium salt.

[0092] A special type of lithium-ion battery is a lithium-polymer battery, in which a polymer electrolyte is used instead of a liquid electrolyte. The electrolyte of a similar solid-state battery may also include other types of solid electrolytes, such as sulfide solid electrolytes, oxide solid electrolytes, or mixtures thereof.

[0093] The battery of the present invention may be a lithium metal battery, such as Li-air, lithium sulfur (Li-S), and other types of lithium metal batteries.

[0094] Li-air batteries usually contain a porous carbon cathode and an organic glass-ceramic or polymer-ceramic type electrolyte.

[0095] Li-sulfur (Li-S) batteries typically contain iron disulfide (FeS2), iron sulfide (FeS), copper sulfide (CuS), lead sulfide and copper sulfide (PbS+CuS) cathodes.

[0096] There are many other known types of lithium metal batteries, such as lithium-selenium (Li-Se), lithium-manganese dioxide (Li-MnO2 or Li / Al-MnO2), lithium-monofluoride (Li-(CF) x ), lithium-thionyl chloride (Li-SOCl2), lithium-sulfuryl chloride (Li-SO2Cl2), lithium-sulfur dioxide (Li-SO2), lithium-iodine (Li-I2), lithium-silver chromate (Li-Ag2CrO4), lithium-vanadium pentoxide (Li-V2O5 or Li / Al-V2O5), lithium-copper chloride (Li-CuCl2), lithium-copper (II) oxide (Li-CuO), lithium-copper oxyphosphate (Li-Cu4O(PO4)2) and other types. BRIEF DESCRIPTION OF THE DRAWINGS

[0097] Figure 1 is a TEM image of zirconium phosphate particles prepared as described in Example 1.

[0098] Figure 2 The XRD pattern of zirconium phosphate prepared as described in Example 1 is shown.

[0099] Figure 3 is a TEM image of zirconium phosphate particles prepared as described in Example 1.

[0100] Figure 4-2 and Comparative Example 1-2.

[0101] Figure 4 SEM image showing NMC dry-coated with zirconium phosphate particles from the vapor phase process

[0102] a) Backscattered electron (BSE) image,

[0103] b) EDX mapping of Zr,

[0104] c) High-resolution SEM image.

[0105] Figure 5 The cycling performance of uncoated NMC and NMC dry-coated with vapor-phase zirconium phosphate particles in lithium-ion batteries with liquid electrolyte is shown. Example

[0106] Example 1

[0107] 2.97 kg containing 1337 g of commercial solution (Octa A solution of zirconium 18) (containing 18.01 wt.% Zr in the form of zirconium ethylhexanoate) and 982 g of a commercial solution (Alfa Aesar) (containing 16.66 wt.% phosphorus in the form of triethyl phosphate) was mixed to give a clear solution. This solution corresponded to the composition of ZrP2O7.

[0108] 1.25 kg / h of this solution and 5 Nm 3 / h of air aerosol and spray it into a tubular reaction with a combustion flame. The combustion gas of the flame is 4.3Nm 3 / h of hydrogen and 25Nm 3 / h of air composition. In addition, using 15Nm 3 After the reactor, the reaction gas is cooled and filtered.

[0109] The BET surface area of ​​the obtained white powder was 36 m 2 / g, and the compacted density is 65g / l. The TEM image of the particles is as follows Figure 1 As shown, and XRD analysis ( Figure 2 ) showed that the main phase of the product was cubic phase of zirconium phosphate. Figure 3 Shown is the aggregate size distribution of the material after 30 min of sonication.

[0110] Example 2: Dry coating of zirconium phosphate (ZPO) on CAM

[0111] In a high-intensity laboratory mixer (SOMAKON mixer MP-GL with 0.5 L mixing unit), a mixture of 1.5 L quartz crystals with a BET surface area of ​​0.30-0.60 m 2 Commercial NMC 7 1.5 1.5-powder (Linyi Gelon LIB Co., PLB-H7 type) with a median diameter of d50 = 10.6 ± 2 μm (via laser scattering) and a corresponding amount (1.0 wt.%) of ZPO powder (according to Example 1) were first mixed at 500 rpm for 1 min to uniformly mix the two powders. The mixing intensity was then increased to 2000 rpm for 5 min to achieve dry coating of the NMC particles with ZPO.

[0112] The coated NMC particles had a ZPO coating thickness of 20-200 nm. Figure 4 SEM images of NMC dry coated with ZPO are shown. Comparison of the backscattered electron image (a) of NMC dry coated with vapor-phase ZPO with the EDX mapping of Zr (b) shows complete and uniform coverage by ZPO around all cathode particles. No larger ZPO agglomerates were detected, indicating that the dispersion of the nanostructured vapor-phase ZPO was successful. In addition, no free, unattached ZPO particles were found next to the cathode particles, indicating strong adhesion between the coating and the substrate. The high-resolution SEM image (c) shows the uniform distribution of ZPO with high surface coverage of CAM.

[0113] Example 3: Electrochemical test:

[0114] Electrodes for electrochemical measurements were prepared by blending 90 wt.% NMC with 5 wt.% PVDF (Solef PVDF5130) as a binder and 5 wt.% SUPER C65 (IMERYS) as a conductive additive under an inert gas atmosphere. N-methyl-2-pyrrolidone (NMP) was used as a solvent. The slurry was cast on an aluminum foil and dried on a hot plate at 120 °C in air for 20 min. Afterwards, the electrode sheet was dried in a vacuum oven at 120 °C for 2 h. The area-dependent positive electrode loading was adjusted to 2.0 ± 0.1 mAh cm -2 Circular electrodes with a diameter of 12 mm were punched out and rolled to achieve 3.0 g cm -3 The electrode density was set at 120 ° C and dried again in a vacuum oven for 12 h to remove any residual water and NMP. For the cycle test, the battery was assembled as a CR2032 type button cell (MTI Corporation) in an argon-filled glove box (GLOVEBOX SYSTEMTECHNIK GmbH). Lithium metal (ROCKWOOD LITHIUM GmbH) was used as the negative electrode material. Celgard 2500 was used as a separator. 35 μL of a 1 mol LiPF6 solution in ethylene carbonate and ethyl methyl carbonate (50:50 wt. / wt.; SIGMA-ALDRICH) was used as the electrolyte. The battery was locked with a crimper (MTI).

[0115] For electrochemical evaluation, at 25 °C, the voltage ranged from 3.0 to 4.3 V vs Li + / Li were cycled at a constant current. For the calculation of capacity and specific current, only the mass of active material was considered and the theoretical capacity of NMC 7 1.51.5 was assumed to be 180 mAh / g. For the button half-cell during cycling, the charge rate was increased every four cycles, starting from 0.1 / 0.1 (charge / discharge) to 0.2 / 0.2, 0.5 / 0.5, 1.0 / 1.0 and 1.0 / 2.0 C. Afterwards, the battery was cycled at 1 / 1 C for long-term stability testing.

[0116] Figure 5 The effect of the as-received ZPO coating on cycle performance is shown. The performance of NMC coated with vapor ZPO is compared to that of uncoated NMC. From the graphical data, it can be intuitively concluded that vapor ZPO coating significantly improves the performance and cycle life of NMC. NMC coated with vapor ZPO shows improved rate performance and long-term cycle stability.

[0117] Measurement of LiOH and Li2CO3 content

[0118] 2g of positive electrode material powder and 30mL of deionized water were placed in a 100mL titration beaker and stirred at room temperature for 10 minutes. The remaining solid was filtered out and the filter was rinsed with 20mL of deionized water. All liquids were collected in a 100mL titration beaker. Tris(hydroxymethyl)aminomethane (TRIS) was used as a standard and the LiOH and Li2CO3 contents were determined by titration with hydrochloric acid (c(HCl)=0.1mol / L). Therefore, the beaker was placed on a manual titration stand (Excellence TitratorT7 from Mettler Toledo, with a 20mL burette DV1020 and electrode DGi111-SC) and titration was started.

[0119] For the material of Example 1, 0.05 wt.% LiOH and 0.265 wt.% Li2CO3 were detected by titration. In contrast, 0.168 wt.% LiOH and 0.511 wt.% Li2CO3 were detected by titration on the uncoated NMC.

[0120] As can be seen from the examples, the zirconium phosphate (ZPO) of the present invention is very suitable for advantageous use as a component of an electrode. In addition to improved performance and cycle life, it is also shown that the material of the present invention is able to reduce the LiOH / Li2CO3 content, thereby emphasizing the lithium ion scavenging ability of the zirconium phosphate of the present invention.

Claims

1. Zirconium phosphate of the general formula ZrP2O7 prepared by pyrolysis, characterized in that The zirconium phosphate - in the form of aggregated primary particles, -BET surface area (DIN 9277:2014) 5m 2 / g-100m 2 / g, -Numerical average particle size d 50 = 0.03 μm - 2 μm, as determined by static light scattering (SLS), and The tapped density (DIN ISO 787-11:1995) is 20 g / L-200 g / L.

2. A method for producing zirconium phosphate according to claim 1 by flame spray pyrolysis, wherein the - at least one zirconium compound chosen from carboxylates, wherein each of these zirconium carboxylates contains 5 to 20 carbon atoms, -organophosphates, - A solution of a solvent containing less than 10% by weight of water is subjected to flame spray pyrolysis.

3. The method according to claim 2, characterized in that The zirconium carboxylate is a carboxylate selected from linear, branched or cyclic zirconium pentanoate (C5), hexanoate (C6), heptanoate (C7), octanoate (C8), nonanoate (C9), decanoate (D10), undecanoate (C11), dodecanoate (C12), tridecanoate (C13), tetradecanoate (C14), pentadecanoate (C15), hexadecanoate (C16), heptadecanoate (C17), octadecanoate (C18), nonadecanoate (C19), eicosanoate (C20) and mixtures thereof.

4. The method according to claim 2 or 3, characterized in that The organic phosphate ester is selected from esters of phosphorous acid (H3PO3), orthophosphoric acid (H3PO4), metaphosphoric acid (HPO3), pyrophosphoric acid (H4P2O7), polyphosphoric acid and mixtures thereof.

5. The method according to claims 2 to 4, characterized in that The organic phosphate ester is selected from the group consisting of alkyl esters, aryl esters, mixed alkyl / aryl esters, and mixtures thereof.

6. The method according to claims 2 to 5, characterized in that The organic phosphate ester is an alkyl ester having an alkyl group of 1 to 10 carbon atoms.

7. The method according to claims 2 to 6, characterized in that The solvent is selected from the group consisting of linear or cyclic, saturated or unsaturated, aliphatic or aromatic hydrocarbons, carboxylic acid esters, ethers, alcohols, carboxylic acids and mixtures thereof.

8. The method according to claims 2 to 7, further comprising heat treating the zirconium phosphate produced by flame spray pyrolysis at a temperature of 600°C to 1300°C.

9. The method of claim 8, further comprising grinding the heat-treated zirconium phosphate.

10. Use of the zirconium phosphate according to claim 1 as a component of a solid electrolyte, as an additive in a liquid or gel electrolyte or as a component of an electrode of a lithium ion battery.

11. An electrode for a lithium ion battery comprising the zirconium phosphate according to claim 1.

12. An electrolyte for a lithium ion battery comprising the zirconium phosphate according to claim 1.

13. A lithium ion battery comprising the zirconium phosphate according to claim 1.

14. The lithium ion battery of claim 13, comprising a liquid or gel electrolyte.

15. The lithium ion battery of claim 14, wherein the battery is a solid state battery.

Citation Information

Patent Citations

  • All-solid-state lithium battery

    JP4982866B2

  • Presursor Organic of Tetravalent Metal Phosphates and Pyrophosphates and Their Use for Electrode Modification and for the Preparation of Composite Membrane for Fuel Cells Working at Temperatures>90c and / or at Low Relative Humidity

    US20070224483A1

  • Method for producing mixed oxide powder comprising lithium, lanthanum and zirconium

    WO2015173114A1

  • Synthesis of nanostructured lithium zirconium phosphate

    WO2021089886A2